ANALYSIS OF THE ENERGY EFFICIENCY OF THE USE OF NATURAL REFRIGERANTS IN THE CONDITIONS OF UZBEKISTAN - Azizov , Dilshod Khabibullayevich; Azizova , Durdonakhon Dilshod qizi; Karabaev , Asatilla Sunatillayevich; Abdullaev, Mirolim Mirabidovich; Zokhidov, Mirakbar Zokir o‘g‘li (Educational Research in Universal Sciences, 2023)
The best available refrigeration and air conditioning (ACC) technology is at least twice as efficient as conventional equipment. Experts estimate that their energy efficiency is currently 50-60% of the theoretical maximum, and there is potential to increase this figure to 70-80% through technological innovation. The replacement of refrigerants proposed by the Kigali Amendment to the Montreal Protocol to phase down Hydrochlorofluorocarbons (HCFCs) and Hydrofluorocarbons (HFCs) provides an opportunity to maximize energy efficiency benefits. Energy efficiency in the RCA sector is the provision of services such as comfort and food preservation, only with less energy. Any indicator of energy efficiency in its essence is the ratio of refrigeration (thermal) power to consumed. It is noted that energy efficiency indicators can be expressed in absolute or specific normalized value. The absolute norm characterizes the consumption of fuel and energy resources in regulated operating conditions (modes). The specific rate characterizes the ratio of the consumption of fuel and energy resources to the generated or consumed energy, manufactured products, performed work in regulated conditions (modes) of operation. Some joint developments co-financed with the United Nations Development Program (UNDP) and stakeholders in the field of refrigeration and air conditioning have been studied and analyzed. The results of these studies are presented.